2020
DOI: 10.7717/peerj.10064
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of the plant roots’ soil-reinforcement based on generalized equivalent confining pressure

Abstract: Background To quantitatively evaluate the contribution of plant roots to soil shear strength, the generalized equivalent confining pressure (GECP), which is the difference in confining pressure between the reinforced and un-reinforced soil specimens at the same shear strength, was proposed and considered in terms of the function of plant roots in soil reinforcement. Methods In this paper, silt loam soil was selected as the test soil, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The root-soil composite improved the τ of the soil through a reinforcement mechanism similar to that of conventional reinforcement materials in reinforced soil. Specifically, the roots interacted with the soil to enhance its strength, resulting in an increase in the τ of the composite compared to bare soil [15]. Under different normal stresses, the τ of the bare soil was less than that of the root-soil composites, which shows that plant roots have a reinforcing effect on soil.…”
Section: Shear Strength Of the Root-soil Composites During Different ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The root-soil composite improved the τ of the soil through a reinforcement mechanism similar to that of conventional reinforcement materials in reinforced soil. Specifically, the roots interacted with the soil to enhance its strength, resulting in an increase in the τ of the composite compared to bare soil [15]. Under different normal stresses, the τ of the bare soil was less than that of the root-soil composites, which shows that plant roots have a reinforcing effect on soil.…”
Section: Shear Strength Of the Root-soil Composites During Different ...mentioning
confidence: 99%
“…Xiong et al [13] performed in situ shear tests to evaluate the effect of vegetation roots on the shear strength of soils. It is generally accepted that slope stability can be improved by the reinforcement effect of plant roots [14,15]. Mohsen et al [16] confirmed that vegetation could effectively reduce shallow landslides but had limited influence on deep landslides.…”
Section: Introductionmentioning
confidence: 99%